Risk-Return Analysis of Select Tax Saving Mutual Funds - Subramaniam, S. Prasanna Kumar (Ilomata International Journal of Tax and Accounting, 2024)
The Indian stock market has been in existence since 1875 bestowing lesser range of instruments from companies to invest their money through general public. Since then, the awareness of investment has gained momentum amongst the general public and investors have become curious and intuitive to park their funds in some instrument to attain or gain profit or handsome returns from companies and the market. With the advent of Unit Trust of India (UTI) being formed during 1964 by a special legislature to function under the regulatory and administrative control of Reserve Bank of India (RBI) , it brought an innovative financial thought to the mechanism of investment by investors. Mutual Fund industry boosted the investors’ confidence that upheld capital appreciation, protection, tax burden and promoted financial stability. The researcher attempted to analyse the risk and returns of select tax savings scheme of mutual funds and point out the best tax saving mutual fund amidst the 11 selected funds using parameters like standard deviation, beta, sharpe ratio and treynor ratios for a period of 90 months from 2016 to 2023 taking Net Asset Values published by AMFI and the closing values of Bombay Stock Exchange Standard & Poor (BSE S & P) Sensex and also by using MS Excel for computing all the parameters manually rather than the already published data by many other sources. It was examined that Quant Tax Direct Plan (Growth Option) has good indicators to prove its performance. The research findings can aide investors’ decision with numerous benefits ranging from savings, returns, gains and risk management.